Ceticismo e fundamentação no sistema de Hegel - Albuquerque Bisneto, Oscar Cavalcanti de (2020)
This thesis aims to examine the nature of the relationship that Hegel establishes with the tradition of skeptical thought. In spite of the real need for an exposition of the appreciation made by the author Phenomenology on modern skepticism, reduced by him to the figure of Schulze, in short, our approach consists in showing the fact that the main arguments of the ancient pyrrhonians play a fundamental role in the whole of Hegelian philosophy and that, far from neglecting, or simply treating the problem of skepticism marginally, Hegel starts from the principle that the only viable form of legitimate philosophical foundation is to take skepticism seriously.